2020
DOI: 10.1021/acs.est.0c03857
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Exposure to Phthalates and Phthalate Alternatives in California Pregnant Women during 2007–2013: Comparison with Other Populations

Abstract: Phthalates with potential adverse health effects are being replaced by other phthalates or phthalate alternatives. Little is known about temporal trends of phthalate exposure in pregnant women in the United States. We quantified 16 metabolites of eight phthalates and di(isononyl) cyclohexane-1,2-dicarboxylate (DINCH) in 656 urine samples collected from 192 California pregnant women in 2007−2013 during their second and third trimesters of pregnancy who participated in the MARBLES (Markers of Autism Risk in Babi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
2
28
1
Order By: Relevance
“…al., 2020), Japan(Suzuki et al, 2010) United States(Shin et al, 2020), Taiwan, China(Hsieh et al, 2020), Iran(Darvishmotevalli et al, 2019) and Israel(Berman et al, 2009); by contrast, the detectable rates measured herein for MMP, MB Z P, and MEOHP are signi cantly lower than those reported in the studies just mentioned. Remarkably, the detectable rate of MOP was observed to vary greatly between studies: the lowest reported values are 0.5%, from a study conducted in Denmark (Tefre et al, 2014), and 63%, from a study conducted in Poland(Polańska et al, 2016), which are signi cantly lower values than that measured herein, 87.1%.…”
contrasting
confidence: 59%
“…al., 2020), Japan(Suzuki et al, 2010) United States(Shin et al, 2020), Taiwan, China(Hsieh et al, 2020), Iran(Darvishmotevalli et al, 2019) and Israel(Berman et al, 2009); by contrast, the detectable rates measured herein for MMP, MB Z P, and MEOHP are signi cantly lower than those reported in the studies just mentioned. Remarkably, the detectable rate of MOP was observed to vary greatly between studies: the lowest reported values are 0.5%, from a study conducted in Denmark (Tefre et al, 2014), and 63%, from a study conducted in Poland(Polańska et al, 2016), which are signi cantly lower values than that measured herein, 87.1%.…”
contrasting
confidence: 59%
“…Pregnant women's exposure to these compounds differed by sociodemographic characteristics and use frequency of products potentially containing these compounds before urine collection. 44−53 In our previous study, 54 we learned that broad social forces may have influenced temporal trends and geographic variations in pregnant women's phthalate exposure. Thus, the same study approach may help identify similar broad social forces related to pregnant women's phenol, paraben, and TCC exposure.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, DiNP was frequently used as a substitute for DEHP 67 and levels of its metabolites have increased in pregnant women in the United States and Europe. 68 The structural similarities that make DiNP a useful substitute may partially explain why these two chemicals show similarly strong associations with preschool ADHD in this study. Third, NPR cases are likely a biased subset of ADHD cases as a whole, representing a higher degree of impairment, underidentifying girls, and requiring both hyperactive and inattentive symptoms.…”
Section: Discussionmentioning
confidence: 73%